The euphemism of good practice or advanced nursing practice - Beatriz Rosana Gonçalves de Oliveira Toso; Maria Itayra Padilha; Karen Lucas Breda
ABSTRACT Objective: To analyze how the focus given nowadays in our country to good practices in the care process as centrality of Nursing offers support to the discussion about the expansion of nurses' performance through advanced practices. Method: This is a theoretical-reflexive article, based on critical reading of studies on the subject, focused on the need to discuss the training of nurses in the perspective of their role expansion. Results: The arguments for both subjects, based on the discussion of the theoretical reference of the two themes: good practices or practice based on evidences, and advanced practice nursing. Final considerations and implications for practice: It is proposed that, in addition to good practices, undoubtedly necessary, the appropriation of advanced nursing practice and the debate about its adoption in the country are fundamental to the new professional challenges facing nursing and the training of human resources for the Unified Health System. The arguments presented lead to the knowledge of the nursing topic of recent dissemination in Brazil, the advanced nursing practice, which can substantially change the nurses' performance in our reality.